Effect of Parasitic Element on 408 MHz Antenna for Radio Astronomy Application - Radial Anwar; Mohammad Tariqul Islam; Norbahiah Misran; Geri Gopir; Baharudin Yatim; Mhd Fairos Asillam (International Journal of Antennas and Propagation)
Antenna is one of the important subsystem components in a radio telescope system. In this paper, analysis on the effect of parasitic element on 408 MHz antenna in a radio telescope system is presented. Higher gain up to 10.24 dBi with reduction on beamwidth size has been achieved by optimizing the position of parasitic element relative to the driven element. The proposed antenna is suitable to be utilized in a transient radio telescope array.